Itogi vystupleniya rossiiskikh sportsmenov na igrakh XXVII olimpiady - Shustin, B. N. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
By the purposes of the given publication there were the summarizing the statement of the Russian team in Olympiad in Sydney, analysis of successes and failures of the Russians in these Olympic games. The combined team of Russia was presented in Sydney by 457 sportsmen. 88 medals: 32 gold, 28 silver and 28 bronze in total were won. The tendencies of Olympic sports development are: 1. The accelerated development of the professional sports, increasing of athletes and sports organizations incomes; 2. The increasing of the quantity of competitive countries; 3. The average age of the sportsmen is increased, that reduces the quantity of the winners in young age.